Promoting Inter-Cultural Relations in the Third Millennium - Yadav, Prabhu Ray (Tribhuvan University Journal, 2020)
The paper aims to shed light on the beauty of inter-cultural relations in the third millennium. It endeavours to uplift the academic disciplines like identity, diversity and culture. A mutual understanding is a well known approach/method to develop the beauty of inter-cultural relations. The purpose of inter-cultural relations study is to strengthen social understanding around the world. Such relations play an important role to implement the national and international awareness. Inter-cultural relations, as an integral part of caste, culture, and religion, enlighten people about the distant and distinct cultural relations outside their own cultures. Such knowledge of inter-cultural relationsem powers people to protect their own cultures too.The concept of inter-cultural relations strengthens our economic, political and social stability. After the end of the bipolar world, inter-cultural relations have expanded our mutual/bilateral relations. The very interaction on inter-cultural relations becomes the cornerstone of international relations. Arguing in favour of intercultural relations is the way to reach the highest of the high path in human development.